Instruments for Assessing Basic Life Support Knowledge in Secondary School Students: A Scoping Review and Expert Panel - Marcos Mecías‐Calvo; Maria Sobrido‐Prieto; Rubén Navarro‐Patón (Journal of School Health, 2026)
ABSTRACT Background Schools are essential settings for teaching Basic Life Support (BLS). However, assessment methods for students vary considerably. Methods A scoping review was conducted following the PRISMA‐ScR guidelines and the Joanna Briggs Institute methodology. The search included the MEDLINE, CINAHL, PsycINFO, ERIC, Scopus, and Web of Science databases. Studies using questionnaires administered to secondary school students were selected. A panel of experts validated the descriptive synthesis of the data. Results Thirty‐six studies were included. Ad hoc questionnaires are the most common and show significant variations in their structure and the dimensions they assess. Detection of cardiac arrest and the use of automated external defibrillators (AEDs) were examined less frequently than cardiopulmonary resuscitation (CPR) techniques. Studies on long‐term knowledge retention are very limited. Most studies focus solely on immediate postintervention assessments. Implications for School Health Policy, Practice, and Equity To ensure uniform and equal training in all educational settings, BLS programs in schools must incorporate all elements of the chain of survival, promote active learning techniques, and employ standardized assessment tools. Conclusions Standardized and psychometrically validated instruments are needed to improve the assessment of BLS teaching in secondary schools.